Corepressor metastasis‐associated protein 3 modulates epithelial‐to‐mesenchymal transition and metastasis. Issue 1 (9th March 2017) - Du, Liang; Ning, Zhifeng; Liu, Fuxing; Zhang, Hao
Abstract: Worldwide, metastasis is the leading cause of more than 90% of cancer‐related deaths. Currently, no specific therapies effectively impede metastasis. Metastatic processes are controlled by complex regulatory networks and transcriptional hierarchy. Corepressor metastasis‐associated protein 3 (MTA3) has been confirmed as a novel component of nucleosome remodeling and histone deacetylation (NuRD). Increasing evidence supports the theory that, in the recruitment of transcription factors, coregulators function as master regulators rather than passive passengers. As a master regulator, MTA3 governs the target selection for NuRD and functions as a transcriptional repressor. MTA3 dysregulation is associated with tumor progression, invasion, and metastasis in various cancers. MTA3 is also a key regulator of E‐cadherin expression and epithelial‐to‐mesenchymal transition. Elucidating the functions of MTA3 might help to find additional therapeutic approaches for targeting components of NuRD.